Pembentukan Karakter Peserta Didik dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan Berbasis Budaya Lokal - Narimo, Sabar; Sutama, S.; Novitasari, Meggy (Universitas Muhammadiyah Surakarta, 2019)
Citizenship Education (Civics) is one of the subjects that can build the character of students in behaving democratically so that each student is expected to be able to become a better person. The main problem obstacle when building students’ character in Civics learning based a local culture is a large number of teaching teachers who have difficulty in making students become more active in learning process and can implement lesson material. The purpose of this research is to develop an effective model of development and management of Civics learning based on local culture to be able to improve the learning outcomes of Muhammadiyah Boyolali Elementary School students in Central Java. The method used in this study is a research and development approach whose results are qualitative. The results of this study are the development of Learning Implementation Plans that integrate the local culture with Civics, which is done by 1) incorporating local culture according to Basic Competencies (BS), 2) developing indicators in order to achieve BS, 3) formulating learning objectives, 4) developing learning materials that are relevant to local culture, 5) developing learning activities that will be carried out, and 6) developing assessment tools that can measure the level of quality of the local culture of students. In this study resulted in a contribution to the improvement of the quality of education which developed to integrate the local culture with Civics learning.